“Bazar Busana Anak”: Penanaman Kecakapan Hidup Berwirausaha dan Keterampilan Berbasis Garment - Lestari, Ayu (Pena Edukasia, 2023)
Sewing skills are the skills most in demand by the majority of the people of Demak. This is because there are many garment and convection companies in the Demak area, such as PT Glory Industrial Park, PT Lucky Textile. Therefore most of the residents of Demak, most of whom are women (Demak in Figures 2022), are very interested in sewing skills. In fact, not only women but men are also starting to be interested in the world of sewing. In making children's clothing there are tools and materials that must be prepared. After the tools and materials are ready, the steps for making clothes are ready to be carried out. After that, make a draft of materials that are used up and also the selling price that will be used. What is expected is that this activity will continue in the future so that the provision of skills for learning residents can become the livelihood of learning residents.